И-Цзин: древняя китайская" Книга Перемен" : текст и комментарий / [перевод Ю. К. Щуцкого] - Щуцкий Ю. К. (ЭКСМО-Пресс, 2001)
Экземпляры: аб. (2002) / Инвентарный номер: 44186 / Цена: / Сис.шифр: 87.3(5) / Авт.знак: И 11 / ГРНТИ: 13.91 / ББК: 87.3(5Кит)3